Analysis or market potential of sago from Agusan del Sur - Tato, Sheen Alexandre F. (2009)
Sago palms are abundant in Agusan del Sur, but are underutilized and considered to have less economic value. At present, sago starch is mainly utilized as a substitute for rice and other rootcrops like camote and cassava and as an ingredient for local delicacies in Agusan del Sur. In the global scenario, sago starch has been used for several products, such as thickener for food, stabilizer in pharmaceuticals, and for other high-value products. This paper examined the market potential of sago palm considering the commercial possibilities of high value food and industrial products that can be made from sago starch and the possible utilization of the local sago palms for these products. Demand and supply condition of sago starch in the local and export market were compared based on the demand and supply models that were constructed. The factors affecting the demand and supply condition of sago starch were also analyzed using the computed demand and supply elasticities. Two types of data were used for the models: primary and cross-sectional data. In constructing the demand and supply models of sago starch in the local markets, primary cross-sectional data were used. On the other hand, secondary time-series data were used for the demand and supply models of sago starch in the export market. The study was able to identify that sago starch is an inferior good in the local markets as consumed by the communities, which is suggested by the negative income elasticity of demand. It was also identified that the price of chemical products in Japan has a positive relationship with the volume of sago starch that they import which suggest that sago starch has a potential in the chemical industry in Japan. To fill the gap in the local sago industry, there is a need for collaboration among the government, academe, private sector, and the local communities in exploring potential markets for sago and developing high-value products from sago starch.
Thesis, Undergraduate (BS Agribusiness Economics) -- U. P. in Mindanao